2014
DOI: 10.1371/journal.pone.0094855
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-143 Targets Syndecan-1 to Repress Cell Growth in Melanoma

Abstract: Melanoma is the most aggressive type of skin cancer with a rapid progression and a limited efficiency of therapeutics. Recently, studies have identified some microRNAs playing important roles in the development of melanoma. Syndecan-1 (Syn-1), dysregulated in many cancers, plays important roles in tumor progression by controlling cell proliferation. In this study, we investigated whether microRNA-143 (miR-143) is involved in the regulation of Syn-1 and thus plays a functional role in melanoma. We found that mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 31 publications
5
37
0
Order By: Relevance
“…Among these dysregulated miRNAs was miR-143 which was downregulated 4.8-fold in the arsenic-transformed prostate SCs, As-CSCs (Ngalame et al 2014b). The downregulation of miR-143 in As-CSCs is consistent with decreased expression of the miRNA in other prostate cancers (Ahmad et al 2013; Clape et al 2009; Xu et al 2011) and other cancer types including cervical (Lipeng et al 2012), lung (Ni et al 2013), gastric (Takagi et al 2009), leukemia (Akao et al 2009; Shen et al 2014), pancreatic (Pramanik et al 2011), melanoma (Li et al 2014), colorectal (Zhang et al 2012), osteosarcoma (Osaki et al 2011), and bladder (Noguchi et al 2011). In some of the above-mentioned studies, miR-143 was shown to act as a tumor suppressor, as restoration of miR143 in these cancer cells significantly reduced cancer cell properties.…”
Section: Introductionsupporting
confidence: 66%
“…Among these dysregulated miRNAs was miR-143 which was downregulated 4.8-fold in the arsenic-transformed prostate SCs, As-CSCs (Ngalame et al 2014b). The downregulation of miR-143 in As-CSCs is consistent with decreased expression of the miRNA in other prostate cancers (Ahmad et al 2013; Clape et al 2009; Xu et al 2011) and other cancer types including cervical (Lipeng et al 2012), lung (Ni et al 2013), gastric (Takagi et al 2009), leukemia (Akao et al 2009; Shen et al 2014), pancreatic (Pramanik et al 2011), melanoma (Li et al 2014), colorectal (Zhang et al 2012), osteosarcoma (Osaki et al 2011), and bladder (Noguchi et al 2011). In some of the above-mentioned studies, miR-143 was shown to act as a tumor suppressor, as restoration of miR143 in these cancer cells significantly reduced cancer cell properties.…”
Section: Introductionsupporting
confidence: 66%
“…Although these downstream targets of miR-143 have been described in other cell lines [11,12], regulation of these proteoglycans by miR-143 in the glomerulus has not been reported previously.…”
Section: Discussionmentioning
confidence: 79%
“…Usually one miR has several targets. MiRs have been reported to regulate the proteoglycans in melanoma and smooth muscle cells [11,12]. Moreover, it has been shown that miRs play a significant role in glomerular diseases [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cell type-specific regulations were consistent with previous findings. For example, miR-143-3p and miR-378a-3p are known to be regulated by TGF-β in non-renal cells [25,26]. Both miRs were also upregulated in cultured human podocytes after stimulation with TGF-β in our miR-screening.…”
Section: Discussionmentioning
confidence: 72%